The Simile Word (Kaaf Al-Tashbeeh) Between The Stability, Problem Of Definition, And Significance - Mesfer Mihmas Aldawsari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The Arabic letter